Prevalence and determinants of obesity among male secondary schools students in Al Bukhiriyah, Qassim region, Saudi Arabia - Khan, Asif; AlRshidi, Bader Abdullah; AlRshidi, Ibrahim Abdullah; Elmosaad, Yousif M.; Jaber, Mahmoud (International Journal Of Community Medicine And Public Health, 2017)
Background: Obesity is a condition associated with the presence of excess fat in the body. It is determined by genetic and environmental factors that are difficult to control when dieting. Methods: The study population consisted of 254 students randomly drawn from five secondary schools which are present in Bukhiriyah and the students were selected using systemic random sampling method. Results: Overweight (21.26%) and obesity (17.72%) was more prevalent in students who used vehicles as mode of transport. Overweight (19.29%) and obesity (15.75%) was more prevalent in students who consumed carbonated drinks. Conclusions: The conclusion of our study was that overweight and obesity were associated with various factors like physical inactivity, soft drink intake, fast food intake and less sleep.